Zooming Into the Ecosystem: Agency and Politics Around Open Data Platforms in Lyon and Berlin - Slobodova, Olga; Becker, Sören (Frontiers in Sustainable Cities, 2020)
Open data platforms provide free access to datasets in key areas of urban development. Often managed by the local state, open data platforms constitute a part of smart city strategies worldwide, serving different, potentially contradictory aims, i.e., fostering economic development, pursuing civic objectives or improving administrative efficiency. Reflecting these diverse orientations, our interest lies in understanding how open data platforms are coproduced by different actors based on their conceptions of open data. Taking a critical stance toward the often functionalistic interpretation of open data initiatives as ecosystems, we conceptualize the development of open data initiatives through a dynamic approach to agency, focusing on the strategies of different actor groups shaping open data initiatives and platforms in specific local governance contexts. Empirically, the paper analyses the development of open data initiatives and platforms in two European cities, Lyon and Berlin. Starting with the initial steps for setting open data on the agenda, we apply a process perspective unpacking actors' conceptions of open data and their strategies to shape open data initiatives and platform design. The analysis is based on tracing development processes and on interviews with representatives of city administrations, open data initiatives and civil society. Our findings indicate the objectives of open data initiatives were narrowed down to economic development and administration efficiency, despite broader visions on open data among other actors. This can be traced back to the high importance of personnel, financial and technical resources for defining the implementation of open data initiatives.